Does AI-based recruitment influence an employer’s attractiveness to potential employees? - Sinha, Aparna (2024)
This research investigates the key factors, specifically the new AI-based Recruitment Process which can affect the Employer’s Attractiveness and Joining Intentions from potential candidate’s perspective in Malaysia. Kaplan and Haenlein (2019) describes AI recruiting as a tech-advanced procedure which helps firms in their recruitment and selection processes. It uses a system’s capability to infer the external data accurately to implement the knowledge gained to attain determined goals with its adaptability. Firms using new, innovative and cutting-edge technologies such as AI, Machine Learning, Deep learning technologies etc. are deemed to be attractive as they have great capabilities to widen the reach of realtime engagements for businesses with its stakeholders and offer business continuity even during challenging times like the pandemic (Watters,2023). AI-tools are highly attractive in the recruitment industry as they offer higher speed, superior business insights, reduce human errors, automate tedious repetitive tasks, provides efficiency gains by increases productivity, candidate experience and is also time and cost saving. Hence, it has emerged as a valued asset over traditional recruitment practices(VanEsch and Black, 2019). Other studies like Gartner, InfoTech Research Group report also suggests that AI and other modern technologies are gaining popularity. HR Managers and Firms thus, need to understand the needs of its potential employees when strategically approaching the job market for competitive advantage and to attract skilled talents to join them.